Teachers' Strategies in Managing PJOK Learning in Elementary Schools to Increase Student Learning Motivation - Devita Sari Purba; Chaterine Anggekia Butar butar; Hizkia Adventy Saragih; Jesica Elsadhay Purba; Olga Griselda Tarigan (Outline Publisher, 2024)
Physical Education, Sports and Health (PJOK) has an important role in shaping students' character and health. This study aims to explore the strategies used by teachers in managing PJOK learning at SDN 060792 with a focus on increasing student learning motivation. The research method used is qualitative research with a case study approach. Data were collected through observation, interviews, and document analysis. The results of the study show that teachers use various strategies, including the use of technology, project-based learning, and the use of a variety of activities to increase students' motivation to learn. This finding has important implications in the development of effective learning strategies in increasing student learning motivation in PJOK learning.